Development Of Critical Thinking Transfer Practice Construct And Sub-constructs: A 9-steps Approach - Noor Azura Mat Said; Siti Mariam Bujang; Nor Aishah Buang; Mohd Nasri Awang Besar; Harlina Halizah Siraj @ Ramli (Education in Medicine Journal, 2024)
Education in Medicine Journal 2021; 13(4): 85–101